A Study on Factors Influencing Hotel Employee's Job Satisfaction: A Case Study of Tang Dynasty Hotel - Ma, Liang (2010)
The purpose of this study was to investigate the factors affecting job satisfaction at Tang Dynasty Hotel in China. In this study, I only refered a case study, because the Tang Dynasty Hotel is the five-star hotel in Xi'an in China, a total of 12 departments, a total of more than 300 employees. The data was collected and administered by means of by Smith,Kendall & Hullin, as Job Descriptive Index(JDI). The study showed that organizational factors such as job itself, work environment, and interpersonal relationship influenced employee job satisfaction in Tang Dynasty Hotel. On the other way round, it was found out that salary and promotion did not really determine the employee's perceived job satisfaction. My case study might be based on effective organizational performance in the Tang Dynasty hotel in China, the hotel employees need to be motivated in terms of the nature of the job, the working environment and interpersonal relationship among the workers. There is need for improvement in these three areas. The findings of this study is of immense benefits to the Tang Dynasty Hotel in China and will enable them to gain better competitive advantage to be able to compete among international five star hotel since the findings will assist the hotel organization to know the best way of satisfying the employees.